CO2 and O2 concentrations in integral motorcycle helmets - Brühwiler, P.A.; Stämpfli, R.; Huber, R.; Camenzind, M. (Applied ergonomics, 2005)
Inhaling air which contains excess CO2 and/or is oxygen-deficient is known to present health risks and to diminish human cognitive abilities. The average CO2 concentrations relevant to a motorcyclist wearing an integral helmet were measured 20 years ago and found to be alarmingly large. The purpose of the present study was to examine gas concentrations typically inhaled by a motorcyclist. Average concentrations of CO2 near the upper lip for persons (n = 4) wearing integral motorcycle helmets were measured in the laboratory and the field to facilitate comparison to previous work, and similarly high average concentrations were found: above 2% when stationary, well below 1% for speeds of 50 km/h or more. Very good agreement was obtained between laboratory and field measurements. Detailed measurements of the time-dependent CO2 concentrations passing through a mouthpiece for mouth-breathing showed inhaled levels slightly over half of the corresponding average concentrations, including 1.3+/-0.3% at standstill, though higher concentrations (4% or more) were inhaled at the beginning of each breath. Opening the visor at standstill had on average no effect. At a speed of 50 km/h the inhaled CO2 concentration resembles that for a person without a helmet in still air, at about 0.2%. The oxygen deficiency is generally equal to the CO2 concentration, and could also contribute negatively to a motorcyclist's cognitive abilities.